(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In the present work, the nonlinear finite element method (FEM) analysis by using package ANSYS V.11 has been carried out to analyze eleven tested RPC deep beams, have dimensions 150mm width, 400 mm depth and 1250 mm total length. The present research objective is to analyze the tested RPC deep beams by using three-dimensional nonlinear finite element (ANSYS Version 11.0) computer program was used in this work. Eight-node brick elements (SOLID 65) are used to represent the concrete and three dimensional (LINK 180) is a spar (or truss) element are used to represent the steel reinforcement and element (SOLID 185) is used for the steel plates modeling. This compare between the numerical and experimental conclusion assured well airworthiness from this numerical analysis and this methodology developable in this study where this maximal distinction rate in this ultimate loading was about below 4.2% to total this tested and analyzed RPC deep beams.